2015
DOI: 10.3109/01612840.2015.1025319
|View full text |Cite
|
Sign up to set email alerts
|

A Synthesis of the Literature on Trauma-Informed Care

Abstract: Patients with a history of traumatic life events can become distressed or re-traumatized as the result of healthcare experiences. These patients can benefit from trauma-informed care that is sensitive to their unique needs. However, despite the widespread prevalence of traumatic life experiences such as sexual assault and intimate partner violence, trauma-informed care has not been widely researched or implemented. The purpose of this synthesis of the literature is to examine existing research on trauma-inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
257
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(260 citation statements)
references
References 44 publications
3
257
0
Order By: Relevance
“…TIC is essentially a systems‐focussed approach that recognizes the pervasiveness and impact of trauma (Bateman et al . ; Kessler ; Reeves ). The TIC approach acknowledges that consumers have a high prevalence of historical trauma, and argues that service providers are in a powerful position to recognize and respond to their trauma (Bateman et al .…”
Section: Introductionmentioning
confidence: 99%
“…TIC is essentially a systems‐focussed approach that recognizes the pervasiveness and impact of trauma (Bateman et al . ; Kessler ; Reeves ). The TIC approach acknowledges that consumers have a high prevalence of historical trauma, and argues that service providers are in a powerful position to recognize and respond to their trauma (Bateman et al .…”
Section: Introductionmentioning
confidence: 99%
“…Trauma-informed care provides a framework for incorporating a safe, empathetic Several studies examined TIC within the SUD treatment programs and the impact on recovery from SUD and trauma (Jason, Olson, Mueller, Walt, & Aase, 2011;Oral et al, 2015;Reevs, 2015). The major theme of a Level III meta-synthesis of the literature on TIC found that in spite of the extensive research on the effects of trauma on physical and mental health, there is limited research and implementation of TIC within diverse settings (Reevs, 2015).…”
Section: Theoretical Framework/evidence Based Practice Modelmentioning
confidence: 99%
“…The major theme of a Level III meta-synthesis of the literature on TIC found that in spite of the extensive research on the effects of trauma on physical and mental health, there is limited research and implementation of TIC within diverse settings (Reevs, 2015). A Level III qualitative study on a unique TIC model for women in sober living housing demonstrated the significant role of incorporating TIC in the recovery process through provision of resources, and provision of tools to aid in daily living (Edwards et al, 2017).…”
Section: Theoretical Framework/evidence Based Practice Modelmentioning
confidence: 99%
“…However, there is a growing body of literature on “trauma-informed care” (TIC) and the use of a “trauma-informed approach” to caring for survivors, with evidence suggesting improvements in post-traumatic symptoms and behavior problems among child survivors, patient-provider relationships [108], and broader improvements in collaboration across sectors [109, 110]. TIC is a commitment from the health care organization and all staff at all levels to reduce the risk of re-traumatizing the child when providing treatment and follow-up services [111, 112].…”
Section: Discussionmentioning
confidence: 99%